Application of metagenomic analysis for detection of the reduction in the antibiotic resistance genes (ARGs) by the addition of clay during poultry manure composting. (April 2019) - Awasthi, Mukesh Kumar; Chen, Hongyu; Awasthi, Sanjeev Kumar; Duan, Yumin; Liu, Tao; Pandey, Ashok; Varjani, Sunita; Zhang, Zengqiang
Abstract: The aim of the study was to reduce relative abundance of antibiotic resistant genes (ARGs) in the poultry manure (PM) compost by adding clay and to determine the mechanism of this effect. Five doses of clay additive [at 0% (T1), 2% (T2), 4% (T3), 6% (T4), 8% (T5) and 10% (T6) based on PM dry weight] were compared to explore the mechanism of reduction in ARGs in the PM compost by the addition of clay. The results confirmed that in the initial raw PM from the breeding farm, the ARG concentrations were 1.7–3.01 times higher than that in the domestic PM. High doses of the clay additive play an important role in reduction in the ARGs and are the main factor responsible for significant variations in ARG abundance between the treatment groups. Therefore, we recommend adding high doses of clay (HDC) as an effective means to reduce the maximum percentage of ARGs in PM compost. A heat map correlation study confirmed that HDC addition during the composting process reduced the bioavailable fractions of toxic metals originating from the chicken feed and significantly impacted ARG dispersion. Graphical abstract: Image 1 Highlights: ARGs profiles were significantly influenced by clay amendment. Higher dosage of clay had the dominant impact on the composting process. Changes in ARGs were governed by the dynamics of potential indigenous bacteria.